Respuesta :

Answer:

[tex]-\frac{2}{3} - (-\frac{3}{4}) = \frac{1}{12}[/tex]

[tex]\frac{5}{6} + \frac{5}{12} = \frac{5}{3}[/tex]

Step-by-step explanation:

Given

[tex]-\frac{2}{3} - (-\frac{3}{4})[/tex]

Required

Solve:

[tex]-\frac{2}{3} - (-\frac{3}{4})[/tex]

Open bracket

[tex]-\frac{2}{3} - (-\frac{3}{4}) = -\frac{2}{3} +\frac{3}{4}[/tex]

Take LCM

[tex]-\frac{2}{3} - (-\frac{3}{4}) = \frac{-8+9}{12}[/tex]

[tex]-\frac{2}{3} - (-\frac{3}{4}) = \frac{1}{12}[/tex]

[tex]\frac{5}{6} + \frac{5}{12}[/tex]

Take LCM

[tex]\frac{5}{6} + \frac{5}{12} = \frac{10+5}{12}[/tex]

[tex]\frac{5}{6} + \frac{5}{12} = \frac{15}{12}[/tex]

Divide by 3/3

[tex]\frac{5}{6} + \frac{5}{12} = \frac{5}{3}[/tex]